Elisabeth of Bohemia on the Soul - Eric Stencil (Journal of Modern Philosophy)
In the 1640’s Elisabeth of Bohemia and René Descartes engaged in a philosophically rich correspondence. The most well-known aspect of the correspondence begins with a question Elisabeth asks Descartes about his account of the interaction between soul and body. This objection, often called the ‘problem of interaction’, has received much attention in contemporary scholarship and this attention frequently focuses on the exchange between Elisabeth and Descartes. Following the lead of Descartes himself, the majority of scholars treat the problem of interaction as the core, or even the entirety, of Elisabeth’s objections to Descartes from this stage in the correspondence. In this paper I argue that the driving force of Elisabeth’s objections to Descartes’ account is not the problem of interaction. Rather, Elisabeth’s objections to Descartes fundamentally concern Descartes’ account of the nature of the soul. While Elisabeth clearly offers the problem of interaction, it is only one of several worries each of which is designed to show that Descartes’ account of the soul is insufficient. I argue that Elisabeth raises three distinct problems to Descartes’ account of the nature of the soul: the causal interface problem, the vapors problem and the principal attribute problem.